Counterfactual thought and causal inference: Facilitation effect and dissociation of activation - Neto, Sofia (2014)
The research about the relationship between counterfactual thought and causal reasoning has produced contradictory evidence about which process facilitates the other. This study investigates the possibility that the processes exert a reciprocal influence over each other, and how different levels of negative emotional impact condition the accessibility of counterfactual thought. Forty two participants were presented a scenario with one of two possible outcomes (one more negative, one less negative), after which they performed a counterfactual and a causal task, structured in a task facilitation paradigm. Results indicate that performing either task facilitates the further performance of the other, revealing a symmetrical order effect. Moreover, there was an interaction effect between the nature of the scenario and the activation of the counterfactual process, reflected in the greater accessibility of the counterfactual task in the more emotionally negative scenario. These findings conform to the postulates of the Symmetrical Facilitation and Dissociation of Activation Model (Senos, 2008).